Swedish marine demosponge fauna (Porifera: Demospongiae) sampled 80 years after Jägerskiöld’s inventory - Raquel PEREIRA; Mats LARSSON; Paco CÁRDENAS; Mikael THOLLESSON (European Journal of Taxonomy)
It has been 80 years since Leonard Axel Jägerskiöld’s thorough marine faunistic inventory of the Swedish west coast (1921-1938), which represents the latest update of the Swedish sponge marine fauna. In this study, we present an update of the demosponge fauna with new specimens collected by the Swedish Taxonomic Initiative expeditions (2007-2008), new dredges (2012-2020), and SCUBA (2018–2020). Identifications were based on morphology and a molecular tree-based approach using the Folmer fragment of coxI, and the D3-D5 region of the 28S rRNA-encoding gene. From the 417 specimens examined, 57 different species were identified, of which five were identified to the genus/family level, eight were new reports for Sweden and one was new to science (Halisarca hansghanssoni sp. nov.). Furthermore, we reinstated the name Hymedesmia dujardinii (Bowerbank, 1866). The Swedish Taxonomic Initiative campaigns aimed to replicate the collecting efforts of the Jägerskiöld’s campaigns, thus making them easily comparable. Using the identified sponges of the Jägerskiöld’s inventory possibly changes in the Swedish sponge fauna over the last 80 years are discussed.